Non-phase-separated 2D B–C–N alloys via molecule-like carbon doping in 2D BN: atomic structures and optoelectronic properties. Issue 35 (31st August 2018) - Ren, Xiang-Yang; Xia, Sha; Li, Xian-Bin; Chen, Nian-Ke; Wang, Xue-Peng; Wang, Dan; Chen, Zhan-Guo; Zhang, Shengbai; Sun, Hong-Bo
Abstract : A new way to overcome the phase-separation problem to fabricate 2D B–C–N via molecule-like carbon doping in 2D BN. Abstract : Two-dimensional (2D) B–C–N alloys have recently attracted much attention but unfortunately, Chemical Vapor Deposition (CVD) B–C–N alloys typically phase separate. In spite of that, our analysis of the B–C–N alloy fabricated by electron-beam irradiation suggests that non-phase-separated B–C–N may in fact exist with a carbon concentration up to 14 at%. While this analysis points to a new way to overcome the phase-separation in 2D B–C–N, by first-principles calculations, we show that these B–C–N alloys are made of motifs with even numbers of carbon atoms, in particular, dimers or six-fold rings (in a molecule-like form), embedded in a 2D BN network. Moreover, by tuning the carbon concentration, the band gap of the B–C–N alloys can be reduced by 35% from that of BN. Due to a strong overlap of the wavefunctions at the conduction band and valance band edges, the non-phase-separated B–C–N alloys maintain the strong optical absorption of BN.